Randomised controlled trial of non-invasive ventilation (NIV) for nocturnal hypoventilation in neuromuscular and chest wall disease patients with daytime normocapnia. Issue 12 (18th November 2005) - Ward, S; Chatwin, M; Heather, S; Simonds, A K
Abstract : Background: Long term non-invasive ventilation (NIV) reduces morbidity and mortality in patients with neuromuscular and chest wall disease with hypercapnic ventilatory failure, but preventive use has not produced benefit in normocapnic patients with Duchenne muscular dystrophy. Individuals with nocturnal hypercapnia but daytime normocapnia were randomised to a control group or nocturnal NIV to examine whether nocturnal hypoventilation is a valid indication for NIV. Methods: Forty eight patients with congenital neuromuscular or chest wall disease aged 7–51 years and vital capacity <50% predicted underwent overnight respiratory monitoring. Twenty six with daytime normocapnia and nocturnal hypercapnia were randomised to either nocturnal NIV or to a control group without ventilatory support. NIV was started in the control group if patients fulfilled preset safety criteria. Results: Peak nocturnal transcutaneous carbon dioxide tension (Tcco 2 ) did not differ between the groups, but the mean (SD) percentage of the night during which Tcco 2 was >6.5 kPa decreased in the NIV group (−57.7 (26.1)%) but not in controls (−11.75 (46.1)%; p = 0.049, 95% CI −91.5 to −0.35). Mean (SD) arterial oxygen saturation increased in the NIV group (+2.97 (2.57)%) but not in controls (−1.12 (2.02)%; p = 0.024, 95% CI 0.69 to 7.5). Nine of the 10 controls failed non-intervention by fulfilling criteria to initiate NIV after a mean (SD) of 8.3 (7.3) months. Conclusion: Patients with neuromuscular disease with nocturnal hypoventilation are likely to deteriorate with the development of daytime hypercapnia and/or progressive symptoms within 2 years and may benefit from the introduction of nocturnal NIV before daytime hypercapnia ensues.